Wanita dalam Islam - Mubarokah, Lulu (Journal of Islamic Studies and Humanities, 2021)
AbstractsIn Islam, there are preferences that said Islam has discriminated between women and man, which is it is gives a loss from woman. But in fact, they who don’t even know about the truth are judging how Islam treating their woman. They gives a negative assume without knowing the reason and the advantages from the Islam law. In fact, most of the Muslim are feels comfortable and keep their activities like usual, without any worries and bridle from the law that have made.AbstrakDalam Islam, pandangan mengenai adanya dikriminasi terhadap perbedaan antara wanita dan pria dianggap sangatlah merugikan para wanita. Padahal, mereka yang tidak mengetahui jelas suatu hukum hanyalah memberikan asumsi negatif terhadap bagaimana Islam memerlakukan para kaum muslimah tanpa mengetahui sebab dan keuntungan dari hukum yang telah dibuat. Pada kenyataanya, banyak dari kaum muslimah sendiri merasa nyaman dan tetap menjalani kehidupannya seperti biasa, tanpa adanya kekangan dari hukum yang telah dibuat.